Development of low-calorie papaya-pineapple jam with added fiber - Padua, Meliah Angeles
The objective of this study was to develop a low-calorie jam with added fiber by the substitution of sucrose by sorbitol and aspartame and by the addition of carrageenan. The original recipe which comprised of 43% sucrose was substituted by different amounts of sorbitol solution and the corresponding amount of aspartame was added to obtain the sweetness of 43% sucrose. The incorporation of carrageenan was done to the sample with 5% sorbitol which was most acceptable based on the result of sensory evaluation. The sample with the highest level of carrageenan was chosen for the rest of the study. The pH of the product was modified to a microbiologically safer pH pf 4.2. Storage of two weeks at room and refrigerator temperature showed that the product was microbiologically stable. The sweetness was not affected by storage at these temperatures. However, storage at extreme temperature had a drastic effect on the microbial load of the product.